Pollinator rarity as a threat to a plant with a specialized pollination system. (17th September 2015) - Phillips, Ryan D.; Peakall, Rod; Retter, Bryony A.; Montgomery, Kirke; Menz, Myles H. M.; Davis, Belinda J.; Hayes, Christine; Brown, Graham R.; Swarts, Nigel D.; Dixon, Kingsley W.
<x xml:space="preserve">Abstract</x> An increasing diversity of highly specialized pollination systems are being discovered, many of which are likely to be vulnerable to anthropogenic landscape modification. Here, we investigate if a specialized pollination system limits the persistence of Caladenia huegelii (Orchidaceae), an endangered species pollinated by sexual deception of thynnine wasps. Once locally common in part of its geographical range, C. huegelii is now largely restricted to small habitat remnants in urban areas. Pollinator surveys coupled with DNA barcoding detected a single pollinator taxon, a small form of Macrothynnus insignis. Phylogenetic analysis revealed that small M. insignis from within the range of C. huegelii are strongly divergent from other wasp populations, suggesting that some reproductive isolation may exist. Although common in intact landscapes outside the range of C. huegelli, small M. insignis individuals were recorded at only 4% of sites in suitable C. huegelii habitat. Accordingly, reproductive success in C. huegelii was low compared with related Caladenia spp., with 33–60% of populations failing to set fruit in any given year. As such, populations are likely to now persist primarily through individual plant longevity rather than reproduction. Due to the low reproductive success of C. huegelii, ongoing human intervention will almost certainly be needed to sustain the species. Future research will need to focus on optimizing hand pollination to maintain reproduction and high seed fitness. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 179, 511–525.